Системные биохимические нарушения при экспериментальном аллергическом энцефаломиелите - Кучмеровская, Т.М.; Гурина, Н.М.; Шиманский, И.А.; Донченко, Г.В.; Супрун, С.М.; Клименко, А.П. (Видавничий дім "Академперіодика" НАН України, 2007)
Reduced levels of total lipids and cholesterol in blood serum were shown after 10 days of experimental allergic encephalomyelitis (EAE) induction. The elevated content of blood serum phospholipids was observed after 18 days of EAE duration. These alterations were accompanied by the progressive increase in both the total proteolytic activity and acid phosphatase activity with a decreasing eﬀect on alkaline phosphatase in blood serum. Compared to control, the blood content of vitamin B12 was twice lower in the period as early as 10 days after EAE induction. Our ﬁndings suggest the presence of system biochemical impairments, which most likely reﬂect the degree of EAE-related destructive changes in brain and may be of signiﬁcance as diagnostic and prognostic criteria for multiple sclerosis management.